Investigating the Role of Root Exudates in Recruiting Streptomyces Bacteria to the Arabidopsis thaliana Microbiome - Worsley, Sarah F.; Macey, Michael C.; Prudence, Samuel M. M.; Wilkinson, Barrie; Murrell, J. Colin; Hutchings, Matthew I. (Frontiers in Molecular Biosciences, 2021)
Streptomyces species are saprophytic soil bacteria that produce a diverse array of specialised metabolites, including half of all known antibiotics. They are also rhizobacteria and plant endophytes that can promote plant growth and protect against disease. Several studies have shown that streptomycetes are enriched in the rhizosphere and endosphere of the model plant Arabidopsis thaliana. Here, we set out to test the hypothesis that they are attracted to plant roots by root exudates, and specifically by the plant phytohormone salicylate, which they might use as a nutrient source. We confirmed a previously published report that salicylate over-producing cpr5 plants are colonised more readily by streptomycetes but found that salicylate-deficient sid2-2 and pad4 plants had the same levels of root colonisation by Streptomyces bacteria as the wild-type plants. We then tested eight genome sequenced Streptomyces endophyte strains in vitro and found that none were attracted to or could grow on salicylate as a sole carbon source. We next used 13CO2 DNA stable isotope probing to test whether Streptomyces species can feed off a wider range of plant metabolites but found that Streptomyces bacteria were outcompeted by faster growing proteobacteria and did not incorporate photosynthetically fixed carbon into their DNA. We conclude that, given their saprotrophic nature and under conditions of high competition, streptomycetes most likely feed on more complex organic material shed by growing plant roots. Understanding the factors that impact the competitiveness of strains in the plant root microbiome could have consequences for the effective application of biocontrol strains.